ENVIRONMENTAL PROTECTION AND MANAGEMENT IN LAW NUMBER 11 OF 2020 CONCERNING JOB CREATION OF MASLAHAH PERSPECTIVE - Arsyik Arsyik; Abd. Qadir Gassing; Hamzah Hasan (International Journal of Islamic Studies, 2022)
The main problem in this research is how to protect and manage the environment in Law no. 11 of 2020 concerning the Creation of Problem Perspectives. This study uses library research that collects materials from previous research. Based on its nature, this research is qualitative. The approaches in this research are the theological, statute, and conceptual approaches. The materials used are the quo laws and books or research results related to the discussion. Data processing techniques describe the object under study, make comparisons, evaluate, and make arguments for the research. The research shows that, first, several provisions for changes in the Job Creation Law on the amendments to Article 18 paragraph (2) and Article 19 paragraph (1) of Law no. 41 of 1999. Both articles were weakened by the Job Creation Law, namely, weakening environmental permits and impacting environmental management, which is not worth maslahah. Second, the abolition of Article 36 and amendments to Article 39 paragraph (2) of Law no. 32 of 2009 weakened the role of the community in protecting their environment. Third, there is an amendment to Article 88 of Law no. 32 of 2009 by the Job Creation Act.